Multiple pregnancies and air pollution in moderately polluted cities: Is there an association between air pollution and fetal growth?. (December 2018) - Mariet, Anne-Sophie; Mauny, Frédéric; Pujol, Sophie; Thiriez, Gérard; Sagot, Paul; Riethmuller, Didier; Boilleaut, Mathieu; Defrance, Jérôme; Houot, Hélène; Parmentier, Anne-Laure; Vasseur-Barba, Marie; Benzenine, Eric; et al.
Abstract: Background: Multiple pregnancies (where more than one fetus develops simultaneously in the womb) are systematically excluded from studies of the impact of air pollution on pregnancy outcomes. This study aims to analyze, in a population of multiple pregnancies, the relationship between fetal growth restriction (FGR), small for gestational age (SGA) and exposure to air pollution in moderately polluted cities. Methods: All women with multiple pregnancies living in the city of Besançon or in the urban area of Dijon and who delivered at a university hospital between 2005 and 2009 were included. FGR and SGA were obtained from medical records. Outdoor residential nitrogen dioxide (NO2 ) exposure was assessed using the mother's address, considering a 50 m radius buffer over the following defined pregnancy periods: each trimester, entire pregnancy and two months before delivery. Logistic regression analyses were performed. Results: This study included 249 multiple pregnancies with 506 newborns. The median of NO2 concentration considering a 50 m radius buffer during entire pregnancy was 23.1 μg/m 3 (minimum at 10.1 μg/m 3 and maximum at 46.7 μg/m 3 ). No association was observed between NO2 and SGA whatever the pregnancy period (the odds ratio (OR) range 0.78 to 0.88). Regarding FGR, the OR associated with an increase of 10 μg/m 3 of NO2 exposure during entire pregnancy was 1.52 (95% Confidence Interval (CI): 1.02–2.26). Similar results were observed for NO2 exposure during the various pregnancy periods. Conclusions: These results are in line with an association between NO2 and fetal growth in multiple pregnancies for an exposure mostly below the threshold set out in European legislation. Highlights: Multiple pregnancies display all the complications of singletons at higher frequencies. All multiple pregnancies from a database of >10, 000 pregnancies were included. FGR was associated with NO2 exposure in multiple pregnancies. SGA was not associated with NO2 exposure in multiple pregnancies.